Kajian atas Relasi Islam dan Demokrasi - Miftahul Huda (UIN Maulana Malik Ibrahim Malang, 2005)
There is a relation between democratic development in Indonesia with Islamic sharia. If we want to include military aspect, it can also depend on Islamic movement. Thus, Islamic concepts have to be the promoter for democratic struggle. However, this role will not be effective if Islam does not hold a dialogue with other forces of politic. Hence, Islam is required to be the democratic religion. Politics in Islam will be discussed in this article along with the explanation about democracy as the equality in Politics. The principles of Islamic democratic are also presented as a part of the realization of humans’ harmony life. It is called harmony life since it has the practices of democratic such as doing discussion, teamwork, and freedom to choose. Perkembangan demokrasi di Indonesia ada relasinya dengan syariat Islam. Kalaupun dimasukkan juga unsur militer, militer pun akan bergantung pada gerak Islam. Dengan demikian, konsep-konsep Islam harus menjadi promotor bagi perjuangan demokrasi. Akan tetapi, peran ini tidak akan efektif selama Islam tidak membuka dialog dengan kekuatan politik lainnya. Karena itu, Islam tetap dituntut menjadi Islam yang demokratis. Islam politik akan menjadi bahasan dalam artikel ini, juga penjelasan tentang demokrasi sebagai kesetaraan politik. Kaidah demokrasi Islam juga dibahas sebagai bentuk realisasi kehidupan harmonis manusia. Disebut hidup harmonis karena menganut praktik demokrasi seperti msuyawarah, kerja sama, dan kebebasan memilih.